Micro-Packs - A Key Tool of Fast Moving Consumer Goods Pull Strategy - Gupta, Sanjeev; Mehra, Preeti (Indian Journal of Marketing, 2010)
Intense competition, lack of unexplored markets and increasing complexities of consumer buying behaviour have lead to the development of new marketing revolution which is all-encompassing the Indian market. The marketing strategy of successful companies today is towards adopting a new concept of "Micro-Packs" to coax the customers to purchase smaller sized versions (Small-Packs) of their premium and mid-priced products, especially daily use consumer goods at reasonably prices by enhancing the affordability of the expensive products at the same budget. Micro- Packs allow expensive brands to be sold at an economical price, provide the manufacturer the benefit of providing the product in a small quantity which enables ease of handling on part of the manufacturer and the customer. Apart from this it saves the manufacturer from the hassles of storage of the product. A new product if launched as a Micro-Pack it can help the manufacturer in cutting down the costs of test marketing and can increase convenience of trying a new product for the customer. Availability of so many Micro-Packs of a product also provides an assortment of brands in the same price bracket for the customer to choose from. It also instigates the element of brand loyalty and stimulates repetitive purchases.